Disorganisasi Keluarga dalam Novel Sunyi Paling Riuh Karya Fajar Sulaiman - Putri, Fani Alria; Zulfadhli, Zulfadhli (Persona: Kajian Bahasa dan Sastra, 2024)
This research aims to determine the forms of family disorganization in the novel Sunyi Terriuh by Fajar Sulaiman, the factors causing family disorganization in the novel Sunyi Terriuh by Fajar Sulaiman, and the impact of family disorganization in the novel Sunyi Terriuh by Fajar Sulaiman. This research uses the theory of literary sociology studies. This research is literary research using descriptive methods. The data source for this research is the novel Sunyi Terriuh by Fajar Sulaiman. The results of this research are forms of family disorganization, namely (a) cancellation, separation, divorce and abandonment and (2) empty membrane families. The factors causing disorganization are divided into two, namely internal factors (from within), namely (a) lack of mature thinking or processing of the household which leads to continuous fighting and loss of harmony in the household, (b) Selfish attitudes, namely attitudes that are more selfish. own interests rather than shared interests (c) busyness problems. The impact of family disorganization (a) makes children stressed, children become violent (b) aggressive, children will lose their role. models, (c) children's education becomes disrupted, and (d) children become easily sensitive.